Development of an Electronic Definition for De-escalation of Antibiotics in Hospitalized Patients. (8th July 2020) - Moehring, Rebekah W; Ashley, Elizabeth S Dodds; Davis, Angelina E; Dyer, April Pridgen; Parish, Alice; Ren, Xinru; Lokhnygina, Yuliya; Hicks, Lauri A; Srinivasan, Arjun; Anderson, Deverick J
Abstract: Background: Antimicrobial stewardship programs (ASPs) promote the principle of de-escalation: moving from broad- to narrow-spectrum agents and stopping antibiotics when no longer indicated. A standard, objective definition of de-escalation applied to electronic data could be useful for ASP assessments. Methods: We derived an electronic definition of antibiotic de-escalation and performed a retrospective study among 5 hospitals. Antibiotics were ranked into 4 categories: narrow-spectrum, broad-spectrum, extended-spectrum, and agents targeted for protection. Eligible adult patients were cared for on inpatient units, had antibiotic therapy for at least 2 days, and were hospitalized for at least 3 days after starting antibiotics. Number of antibiotics and rank were assessed at 2 time points: day of antibiotic initiation and either day of discharge or day 5. De-escalation was defined as reduction in either the number of antibiotics or rank. Escalation was an increase in either number or rank. Unchanged was either no change or discordant directions of change. We summarized outcomes among hospitals, units, and diagnoses. Results: Among 39 226 eligible admissions, de-escalation occurred in 14 138 (36%), escalation in 5129 (13%), and antibiotics were unchanged in 19 959 (51%). De-escalation varied among hospitals (median, 37%; range, 31–39%, P  < .001). Diagnoses with lower de-escalation rates included intra-abdominal (23%) and skin and soft tissue (28%) infections. Critical care had higher rates of both de-escalation and escalation compared with wards. Conclusions: Our electronic de-escalation metric demonstrated variation among hospitals, units, and diagnoses. This metric may be useful for assessing stewardship opportunities and impact. Abstract : De-escalation of antibiotics is a key principle of antibiotic stewardship, yet there is no standard definition. We proposed an objective, electronic definition of antibiotic de-escalation and present the distribution among infection diagnoses and its variability among hospitals and units.